Holm oak (Quercus rotundifolia Lam.) and Aleppo pine (Pinus halepensis Mill.) response to different soil preparation techniques applied to forestation in abandoned farmland - Bocio, Inmaculada; Navarro, Francisco Bruno; Ripoll, María Angeles; Jiménez, María Noelia; Simón, Estanislao De (Ann. For. Sci., 2004)
This paper evaluates the effectiveness of several soil preparation procedures in forestation establishment and development in localized farmland, within a territory in ombroclimatic transition between dry and semi-arid, located in Granada, southeastern Spain. An experiment in the forestation of Holm oak (Quercus rotundifolia Lam.) and Aleppo pine (Pinus halepensis Mill.) was set up, in which 8 different soil preparation techniques were used. The survival, total height and basal diameter of the plantation was monitored over a 5-year period (1996-2000). The statistical analysis of these parameters evidenced highly significant differences in the overall behaviour of the two sample forest species, related to changes in the prevailing environmental conditions in these territories and the type of soil preparation procedure applied. The overall results obtained for the three parameters analysed show the effectiveness of using backhoes for pit planting and linear rippering with a hydraulic structure to captures runoffs, in comparison to other preparations. Areal soil preparations, in particular, are not recommended.
Keywords: forestation; semi-arid; soil preparation